An assessment of the likely acceptability of vaginal microbicides for HIV prevention among women in rural Ghana - Abdulai Martha A; Baiden Frank; Adjei George; Afari-Asiedu Samuel; Adjei Kwame; Tawiah Charlotte; Newton Sam (BMC, 2012)
Abstract Background The findings of the CAPRISA tenofovir studies have raised expectations that soon an approved microbicide would be available. However it is in only a limited number of countries in sub-Saharan Africa that the acceptability of microbicides has been evaluated. We conducted a study to assess the acceptability of vaginal microbicides among women in rural Ghana. Methods The study employs a mixed method design, using cross-sectional survey and focus group discussions to further understand issues related to awareness and attitudes towards microbicide development, acceptability and perceived partner attitudes among pregnant women attending antenatal clinic in two health facilities in the Kintampo North municipality of Ghana. We used logistic regression to identify possible predictors of microbicide acceptability among the women surveyed. Results Although only 2% of the 504 women were aware of the development of microbicides, 95% were willing to use one when it became available. The cost of a microbicide that will be considered affordable to 50% of women was US$0.75. Although there were concerns about possible wetting effect, gel or creams were the most preferred (68% of women) formulation. Although 71% thought their partners will find microbicide acceptable, apprehensions about the feasibility of and consequences of failed discreet use were evident. 49% of women were concerned about possible negative effect of microbicide on sexual pleasure. Perceived partner acceptability (O.R. =17.7; 95%C.I. 5.03-62.5) and possibility of discreet use (O.R. =8.9 95%C.I. 2.63-30.13) were the important predictors of microbicide acceptability. Conclusion Achieving microbicide acceptability among male partners should be made a part of the promotive interventions for ensuring effective use among women in rural Ghana.